Community trauma exposure and post-traumatic stress disorder in Chinese children and adolescents - Yuan, Ting; Li, Xiangdong; Liu, Haiyang; Guo, Lei-lei; Li, Jin-long; Xu, Guang; Li, Xiaoping; Sun, Lu; Wang, Congzhi; Yang, Liu; Zhang, Dongmei; Hua, Ying; et al. (Frontiers in Psychiatry, 2023)
Background: An increasing number of studies had shown the association between traumatic events occurring in childhood and adolescence and post-traumatic stress disorder (PTSD). A gap remains in the literature on the epidemiology and influencing factors of traumatic events and post-traumatic stress disorder in communities in northern China. The aims of the study were to determine the prevalence of traumatic events and PTSD in communities in northern China, to explore the types of stressful traumatic events and the impact of these traumatic events on children and adolescents, and to investigate the effect of sociodemographic factors on PTSD. Methods: A cross-sectional survey study was conducted among 6027 students (7-17 years old) from 6 cities in Liaoning provinces, China. The sample consisted of 2853 males (47.34%) and 3174 females (52.66%). Essen Trauma-Inventory for Children and Adolescents (ETI-CA) Scale was used. The ETI-CA has 5 sections, which include type of traumatic event, worst traumatic event, posttraumatic symptoms, onset, duration, burden of PTSD, and present difficulties in different areas of life. PTSD symptoms were assessed with 23 items in Part 3 of the ETI-CA. Results: We found that 2068 (34.3%) of 6027 participants experienced trauma event and 686 (33.2%) of 2068 reported PTSD. Among trauma-exposed youth (2068), the sudden death of close relatives (33.9%), serious accident (20.9%), and parental divorce (15.5%) were reported as the worst traumatic events. Studies have shown that after exposure to stressful life events, more than 30% of people feel nervous or upset (39.8%), scared (33.4%), helpless (32.6%), and about 10% have headaches (15.5%), rapid heartbeat (13.3%), and dizziness (11.8%). Multi-variable logistic regression analyses showed that students of middle school (OR=1.29 (1.016,1.637), not a student leader (OR =0.738 (0.618, 0.881), and their parents in single marital status significantly predicted higher PTSD prevalence (the remarried (OR =0.474 (1), married (OR=0.42 (0.227, 0.778)). Conclusions: The present study suggests that the government to train psychological counselors in schools and communities to provide emotional and psychological support. The school leaders and parents to elevate adolescents’ psychological suzhi. Particularly, counselling and professional support should be given to those students whose parent’s is single.